Distance preferences in the arrangement of binding motifs and hierarchical levels in organization of transcription regulatory information - Makeev, Vsevolod J. (Oxford University Press, 2003)
We explored distance preferences in the arrangement of binding motifs for five transcription factors (Bicoid, Krüppel, Hunchback, Knirps and Caudal) in a large set of Drosophila cis-regulatory modules (CRMs). Analysis of non-overlapping binding motifs revealed the presence of periodic signals specific to particular combinations of binding motifs. The most striking periodic signals (10 bp for Bicoid and 11 bp for Hunchback) suggest preferential positioning of some binding site combinations on the same side of the DNA helix. We also analyzed distance preferences in arrangements of highly correlated overlapping binding motifs, such as Bicoid and Krüppel. Based on the distance analysis, we extracted preferential binding site arrangements and proposed models for potential composite elements (CEs) and antagonistic motif pairs involved in the function of developmental CRMs. Our results suggest that there are distinct hierarchical levels in the organization of transcription regulatory information. We discuss the role of the hierarchy in understanding transcriptional regulation and in detection of transcription regulatory regions in genomes.